Children with Hirschsprung disease in a developing country: A cohort study of the predictors of a positive rectal biopsy result. Issue 46 (18th November 2022) - Al-Taher, Raed; Daradkeh, Hebah Tawfiq; Hadadin, Hiba; Obiedat, Abdelrahman; Hijazein, Yazan; Hijazein, Laith; Obiedat, Sarah; Hadadin, Yazeed; Al Manasra, Abdel rahman; Alduraidi, Hamza; Juweid, Malik
Abstract : Chronic constipation, which may be habitually or pathologically caused, is one of the most common complaints in children. One of the important pathological causes is Hirschsprung's disease (HD), which is diagnosed via multiple modalities, mainly rectal biopsy. Our aim was to compare the presentation and different predictive factors for positive rectal biopsy results in a developing country in the Middle East, such as Jordan. This cohort study was conducted at the Jordan University Hospital (JUH). All consecutive children aged <14 years who presented with refractory constipation and underwent rectal biopsies between January 2014 and December 2019 were retrospectively enrolled in the study. In the entire cohort study, 79 patients were enrolled: 45 (57%) were males and 34 (43%) were females. Regarding the biopsy results, 51 (64.6%) cases of refractory constipation without HD and 28 (35.4%) patients with refractory constipation with HD were diagnosed with open rectal biopsies. The male-to-female ratio of HD patients was 3:1. Moreover, 3 (10.7%) children who passed the meconium within the first 24 to 48 hours showed features of HD, while 17 (60.7%) children with delayed passage of the meconium showed features of HD. Abdominal distension was found to be a positive predictor of positive biopsy results (odds ratio [OR] = 4.09, P  = .011), and soiling was found to be a negative predictor of positive biopsy results (OR = 0.07, P  = .024). In developing countries, children presenting with HD seem to have similar symptoms and signs to those observed with traditional sampling and staining techniques.